Problems and prospects of the interaction of the Constitutional Court of the Republic of Belarus and courts of general jurisdiction in the sphere of approval of constitutional legality - Sinitsyna, Anna M. (Journal of the Belarusian State University. Law, 2019)
The article deals with the problems of interaction between the Constitutional Court of the Republic of Belarus and the courts of general jurisdiction in the area of constitutional legality. The circumstances that impede the implementation of the provisions of part two of article 112 of the Constitution of the Republic of Belarus in practice are analyzed, and legislative options for their elimination are proposed. Special attention is paid to justifying the need to introduce the institution of a preliminary ruling in the Republic of Belarus and review the role of the Supreme Court of the Republic of Belarus in the mechanism provided by the second part of article 112 of the Constitution of the Republic of Belarus.